Microbial Production of Retinyl Palmitate and Its Application as a Cosmeceutical - Bo Hyun Choi; Hee Jin Hwang; Ji Eun Lee; Soon Hwan Oh; Jae Sung Hwang; Bun Yeoul Lee; Pyung Cheon Lee (MDPI AG, 2020)
Chemically synthesized retinyl palmitate has been widely used in the cosmetic and biotechnology industry. In this study, we aimed to demonstrate the microbial production of retinyl palmitate and the benefits of microbial retinyl palmitate in skin physiology. A heterologous retinyl palmitate biosynthesis pathway was reconstructed in metabolically engineered Escherichia coli using synthetic expression modules from Pantoea agglomerans, Salinibacter ruber, and Homo sapiens. High production of retinyl palmitate (69.96 ± 2.64 mg/L) was obtained using a fed-batch fermentation process. Moreover, application of purified microbial retinyl palmitate to human foreskin HS68 fibroblasts led to increased cellular retinoic acid-binding protein 2 (CRABP2) mRNA level [1.7-fold (p = 0.001) at 100 μg/mL], acceleration of cell proliferation, and enhancement of procollagen synthesis [111% (p < 0.05) at 100 μg/mL], strongly indicating an anti-ageing-related effect of this substance. These results would pave the way for large-scale production of retinyl palmitate in microbial systems and represent the first evidence for the application of microbial retinyl palmitate as a cosmeceutical.